Satisfaction, HR, and open innovation in tourism sector - Adya Hermawati; Nurwati Nurwati; Suhana Suhana; Zaky Machmuddah; Shujahat Ali (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The aim of this research paper is to depict the level of satisfaction and importance of Full expressions Micro, Small & Medium Enterprises' (MSMEs)' human resources (HR) and the tourism sector community in East Java. The research was conducted on all aspects of HR in tourism sector MSMEs, among foreign and domestic tourists in East Java. The research is a quantitative and descriptive one. Primary data are used. The population of the research is HR in tourism sector MSMEs as well as domestic and foreign tourists. The sampling technique used is purposive sampling. Ten cities of high tourism potential were chosen. Determination of the sample size used the minimum criteria of a structural model that is between 100 and 200 units. In total, 200 tourism sector MSMEs were determined from ten tourism cities in East Java. From every tourism sector MSMEs, four employees and three tourists were taken. As a result, the entire research consisted of 800 employees and 600 foreign and domestic tourists. Importance performance analysis (IPA) was utilized as an analysis tool in this paper. The result indicated that each tourism resort, being a sample, has different findings. Batu City demonstrates a lack of transglobal leadership (TL). Malang, Kediri, and Blitar City demonstrate organizational citizenship behavior (OCB). Malang City lacks employment engagement (EE). Meanwhile, Pasuruan City and Blitar Regency are about human resources performance (HRP). For Pasuruan Regency, the variable of quality of work life (QWL) should be improved. For Sidoarjo Regency, sustainable tourism competitiveness (STC) should be paid attention. For Kediri City, the main variable that needs to be enriched is responsible marketing (RM). Overall, for the East Java region, the main variable that needs to be improved is RM. The findings obtained constitute a practical contribution for main tourism stakeholders to formulate relevant policies to cope with problems.
Keywords: 650; human resources in tourism; IPA; MSMEs